Development of Refusion Learning Media on Function Material for Class XI MA Students - Nur Fadilah; Arini Hidayati (Civiliza Publishing, Indonesia., 2026)
Mathematics is one of the subjects that has an important role in the development of logical, systematic, critical, and creative thinking skills of students. This research aims to develop valid, practical, and effective REFUSI (Relations and Functions) learning media for grade XI MA Lubbul Labib students. This research is motivated by low learning motivation and students' understanding of the concept of function, especially in determining domains, codomains, and ranges. The research method used is Research and Development (R&D) with the Plomp development model which consists of three stages, namely preliminary research, prototyping phase, and assessment phase. The subjects of the study were 26 students of class XI A MA Lubbul Labib. The research instruments include validation sheets, student response questionnaires, and learning outcome tests. The results of the study showed that the REFUSI media obtained a validity score of 3.42 with the valid category, a practicality score of 3.4 with the practical category, and a student learning completeness level of 96% which indicates the effective category. Based on these results, the REFUSI learning media meets the criteria of valid, practical, and effective so that it is suitable for use in learning mathematics in functional materials